Expression of Escherichia coli pabA. - Tran, P V (1991)
Escherichia coli pabA encodes the glutamine amidotransferase subunit of p-aminobenzoate synthase. p-Aminobenzoate synthase catalyzes the conversion of chorismate and glutamine to 4-amino-4-deoxychorismate, which is then converted to p-aminobenzoate by a 4-amino-4-deoxychorismate lyase. The 5'-terminal segment of pabA was previously shown to be transcribed from two different promoters, one near the pabA coding sequence (P1) and one preceding fic (P2). However, a pabA-lacZ translational fusion was expressed only from the mRNA originating at P1. We have determined that expression of a pabA-lacZ chromosomal fusion is not changed by p-aminobenzoate limitation, growth rate, catabolite repression, overexpression of either p-aminobenzoate synthase subunit, or gene dosage of pabA and pabB. The lack of pabA expression from P2 appears to be the result of a stable secondary structure in the intergenic space preceding pabA that sequesters the pabA ribosome binding site. Disruption of the secondary structure by mutation allowed expression of pabA from P2, as did translation of ribosomes into the fic-pabA intergenic region.